Penerapan Green School Sebagai Penguatan Pendidikan Karakter Anak Usia Dini - Riska, Purnama; Sabani, Fatmarida; Hasis, Pertiwi Kamariah; Yusuf, Munir; Hutami, Eka Poppi (YAYASAN YASZOY CAYAHA NUSANTARA, 2024)
This research aims to describe the description of the Green School at the Al Ikhsan Islamic Kindergarten, Palopo City, to describe Green School activities that can strengthen early childhood character education at the Al Ikhsan Islamic Kindergarten, Palopo City. The approach used in this research is a qualitative approach, in the process of data collected through observation, interviews and documentation. The data analysis used in this research is reduction, data presentation, and drawing conclusions. The results of this research show that 1) the description of the Green School in the Al Ikhasan Islamic Kindergarten in Palopo City is carried out with various environmentally friendly activities such as throwing rubbish in its place, caring for plants around the school, not damaging the school environment, carrying out school greening such as farming activities, saving money in use water so as not to damage the environment around the school. 2) Green School activities at the Al Ikhsan Islamic Kindergarten in Palopo City can strengthen early childhood character education, such as the character of responsibility, discipline, creativity and caring for the environment.